Linking green supply chain management and blockchain technology to green marketing and environmental performance: the mediating role of green technology innovation - Keskin, Halit; Tatoglu, Ekrem; Akgun, Ali E.; Esen, Emel (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeDrawing on the dynamic capabilities view and the practice-based view, this study develops a conceptual model to empirically test the interrelationships between green supply chain management (GSCM), blockchain technology (BCT), and their impact on green marketing and environmental performance. Special attention is given to the mediating role of green technology innovation (GTI) in these relationships.Design/methodology/approachData were collected from 281 respondents, comprising managers and executives from diverse functional areas, across 93 firms in T & uuml;rkiye, a key emerging market. The mediating effects of GTI were tested using Hayes' PROCESS macro (Model 4), providing robust insights into the dynamics of GSCM and BCT in driving sustainability.FindingsThe results confirm that BCT positively influences GSCM, reinforcing the role of digital technologies in enhancing sustainability. The study further reveals that GTI significantly mediates the relationship between GSCM and environmental performance, suggesting that firms can enhance their environmental outcomes by adopting innovative, eco-friendly technologies. Additionally, the mediating role of GTI is evident in the relationship between BCT and both environmental and green marketing performance, highlighting the importance of technological integration in sustainability efforts.Research limitations/implicationsWhile the study provides valuable insights, its focus on firms in T & uuml;rkiye may limit the generalizability of the findings to other regions. Future research could explore these relationships in other emerging economies and examine additional mediating or moderating variables, such as organizational culture or regulatory pressures, to provide a more detailed understanding of the dynamics between BCT, GSCM, and firm performance.Practical implicationsThe findings provide actionable insights for managers, particularly in emerging markets. By adopting BCT, firms can improve supply chain transparency and efficiency, while enhancing both environmental sustainability and marketing performance. Integrating GTI into GSCM practices helps firms meet regulatory demands and gain a competitive advantage in eco-conscious markets.Originality/valueThis paper contributes to the limited literature on the intersection of BCT, GSCM, and firm performance, particularly within the underexplored context of T & uuml;rkiye. It provides a unique perspective on how emerging technologies and green innovations can be harnessed to achieve both environmental and marketing outcomes.
Keywords: Green supply chain management; Blockchain technology; Green marketing performance; Environmental performance; Green technology innovation; T & uuml; rkiye; CIRCULAR ECONOMY CAPABILITY; OF-FIT INDEXES; INSTITUTIONAL PRESSURES; OPERATIONAL PRACTICES; DYNAMIC CAPABILITIES; NATIONAL CULTURE; INDUSTRY 4.0; IMPACT; RESOURCE; FIRM; Business & Economics